Beating burnout at work why teams hold the secret to well-being and resilience - Davis, Paula (Ascent Audio, 2022)
Burnout has become one of the most talked about workplace topics, and its impact is far-reaching. The 24/7 pace of work, constant demands, and scant resources can easily put busy professionals on a path to burnout, a cycle that has only accelerated during the COVID-19 pandemic. Burnout affects the health and well-being of the entire organization, yet most attempts to help focus on quick-fix strategies aimed at individuals. Something is missing. In Beating Burnout at Work, Paula Davis, founder of the Stress & Resilience Institute, provides a new framework to help organizations prevent employee burnout. Davis's research-driven, actionable book is the first of its kind to explore a new solution to the burnout problem at work: a comprehensive approach focused on building the resilience of teams of all sizes. Beating Burnout at Work explores: how Davis navigated her own burnout as a lawyer, and how that led her to launch a business with the aim of helping organizations and their employees become more resilient; how teams and leaders can utilize simple, science-backed strategies to create cultures that promote resilience and well-being and reduce burnout; how the Mayo Clinic has developed a powerful model to reduce burnout in its organization; how organizations dealing with high-stress challenges, including the US Army, work to increase resilience in a systemic way; and more.
Online resource; title from title details screen (O'Reilly, viewed May 3, 2022)
Keywords: Burn out (Psychology) -- Prevention; Work -- Psychological aspects; Resilience (Personality trait); Teams in the workplace; Travail; Aspect psychologique; Résilience (Trait de personnalité); Équipes de travail; Burn out (Psychology); Prevention; Work; Psychological aspects; Downloadable audio books; Audiobooks; Livres audio